Prevalence of Post-Concussion and Post-Traumatic Stress Symptoms One Month after Mild TBI: A Descriptive Observational Study - Mulyadi Mulyadi; Lenny Gannika; Rizki Rivaldo Najoan; Rahmat Hidayat Djalil; Santo Imanuel Tonapa (Faculty of Nursing, Universitas Pelita Harapan, 2025)
Mild traumatic brain injury (mTBI) frequently leads to post-concussion symptoms (PCS) and post-traumatic stress disorder (PTSD), both of which may hinder recovery if not identified early; however, research on these conditions remains limited. This study aimed to determine the prevalence of PCS and PTSD one month after mTBI and to describe demographic and clinical characteristics, including age, gender, education, employment, injury mechanism, and comorbidities. This study employed adescriptive observational design using descriptive statistics. A purposive sampling technique recruited 65 patients based on predefined inclusion and exclusion criteria. PCS was measured using the Rivermead Post-Concussion Symptoms Questionnaire, and PTSD was assessed using the PTSD Checklist for DSM-5. Data were collected from August to November 2024 at Prof. Dr. R.D. Kandou Hospital, Manado, North Sulawesi. Descriptive statistics were applied to analyze PCS, PTSD, and demographic characteristics. The results reported that of 65 patients with mild traumatic brain injury (mean age 30.69 years, 67.7% male), most had >9 years of education (60.0%) and were unemployed (61.5%). Motor vehicle crashes were the leading cause of injury (46.2%). One-month post-injury, 33.8% experienced post-concussion symptoms and 21.5% reported symptoms of post-traumatic stress disorder. Conclusion, PCS and PTSD are common in the early phase after mTBI, particularly among young men and those injured in motor vehicle crashes. These findings highlight the importance of early symptom recognition, patient education, and psychological support, as well as strengthened road safety measures to reduce the impact of mTBI.